Feasts of Raw Meat - Harris, Russell (Petits Propos Culinaires, 2024)
Russell Harris is a free-lance translator currently living in Amsterdam. He also works under the auspices of the Lafayette Project and it was while cataloguing a group of photographs of Ras Makonnen for the Victoria and Albert Museum that he happened upon the early reports of Abyssinian culinary habits which had horrified readers in the past. He decided to investigate these, and here exposes some misconceptions which in his view flawed the reports and exaggerated the barbaric aspects of the practices.